Farming out of place: Transnational family farmers, flexible farming, and the rupture of rural life in Bahia, Brazil. (21st August 2018) - OFSTEHAGE, ANDREW
ABSTRACT: North American soybean farmers have responded to farmland inaccessibility in the US Midwest by purchasing and operating large soybean farms in western Bahia, Brazil. They have turned to "flexible farming" and flexible crops, labor, and land that are commodified, replaceable, and alienated from social and physical relations. Nevertheless, temporalities of farming survive, redefined in terms of progress and backwardness, and new materialities and models of farming emerge. This emergent agrarianism is flexible in terms of fungible means of production and farmer subjectivities that push the boundaries of "family farming." The detachment and mobility of things and people in global agricultural production disrupts rural life and generates values and practices as farmers engage with the land and make meaning out of transnational farming. [ flexibility, work, land, crops, transnationalism, agriculture, Brazil, United States ] Abstract : Seemingly endless tracts of soy and cotton are broken up by patches of Brazilian savannah known as the Cerrado, outside the city of Luís Eduardo Magalhães in Bahia, Brazil (November 6, 2014).